THE INFLUENCE OF SERVICE QUALITY AND PRICE ON PURCHASING DECISIONS THROUGH CUSTOMER SATISFACTION AS MEDIATION IN RETAIL BUILDING STORE IN SEKAYU CITY - Sari, Rossaria; Rahayu, Sri; Nurrahmi, Maftuha (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research aims to determine the Influence of Service Quality and Price on Purchase Decisions Through Customer Satisfaction as Mediation in Retail Building Stores in Sekayu City. This type of research is Associative. The variables used by the researcher were the variables of service quality, price, satisfaction and purchase decisions. The sample in this study is Customers as Mediation in Retail Building Stores in Sekayu City which amounted to 100 people who were selected by Accidentail Sampling. The data used in this study is primary data with a questionnaire data collection method. The data analysis technique used is Structural Modeling Equation (SEM) with the Lisrel Program Application. The results of this study show that: (1) Service quality has a significant effect on Customer Satisfaction in Retail Building Stores in Sekayu City. (2) Price has an effect but not significantly on Customer Satisfaction at Retail Building Stores in Sekayu City. (3) Service quality has a significant effect on Purchase Decisions at Retail Building Stores in Sekayu City. (4) Price has an effect but not significantly on the Purchase Decision at Retail Building Stores in Sekayu City. (5) Customer Satisfaction has a Significant Effect on Purchase Decisions at Retail Building Stores in the City of Sekayu Consumer.